Perspectives on Richard Ford - Guagliardo, Huey (Book collections on Project MUSE., 2000)
A comprehensive appreciation of the fiction written by this Pulitzer Prize author This is the first book-length examination of the fiction written by Richard Ford, who gained critical acclaim for The Sportswriter, the story of suburbanite Frank Bascombe's struggle to survive loneliness and great loss. That novel, published in 1986, struck a chord with readers and reviewers alike, and Ford, a little-known writer who had for a time considered giving up the writing of fiction, was suddenly hailed in Newsweek as "one of the best writers of his generation." The Sportswriter, along with its 1995.